Effect of salt stress on seed and seedling characters of tomato (Lycopersicum esculentum) genotypes (Current Horticulture, 2024)
To alleviate the deleterious effects of salinity, reclamation of salinized lands, improvement of irrigation with saline water and the cultivation of salt tolerant variety have been applied. The positive changes as crop cultivars, local climate, soil nutrients, type of salt, salinity levels, irrigation methods and water management practices (Datta et al., 2015). However, information on effect of salinity on seed germination, shoot length, root length, seedling length, vigour index etc. is limited. Therefore, experiment was conducted to evaluate tomato genotypes with different concentration of NaCl.